2003
DOI: 10.1159/000069395
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of IL-18 and Soluble Fas in Patients with Postoperative Hepatic Failure

Abstract: We measured the levels of tumor necrosis factor alpha (TNF-α), interleukins (IL)-6 and -18, and soluble Fas (sFas) in 11 patients with postoperative hepatic failure and assessed whether IL-18-mediated apoptosis is involved in the onset of liver dysfunction. The serum TNF-α, IL-18, and sFas levels were significantly higher in patients with sepsis as a complication than in those without sepsis. The TNF-α and IL-18 levels were significantly higher in nonsurvivors than in survivors. Significant correlations were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Marino et al [26] in their study showed that the pro-apoptotic role of IL-18 on liver endothelial cells is not related to Fas-mediated apoptosis, and the cell death is mediated via TNFRI. Nakae H et al [18] showed the raising serum levels of IL-18 and sFas in patients with postoperative hepatic failure. They suggested that IL-18 has both pro-apoptotic and anti-apoptotic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marino et al [26] in their study showed that the pro-apoptotic role of IL-18 on liver endothelial cells is not related to Fas-mediated apoptosis, and the cell death is mediated via TNFRI. Nakae H et al [18] showed the raising serum levels of IL-18 and sFas in patients with postoperative hepatic failure. They suggested that IL-18 has both pro-apoptotic and anti-apoptotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [16] showed that the percentage of peripheral blood apoptotic lymphocytes after a 24 h of incubation with recombinant human IL-18 was significantly higher compared to the percentage at time zero of incubation in adult onset still's disease (AOSD), SLE and healthy participants. There are a few studies reporting the correlation between sFas and IL-18 in hepatic diseases [17,18] and pulmonary complications in tuberculosis [19]. To explore the existence of the correlation between sFas, an apoptotic marker, and IL-18, a proapoptotic cytokine, serum concentration in SLE, this study was designed in a large group of lupus patients in different stages of disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many hepatocellular functions are altered by sepsis, and hepatic histopathological changes, such as mid‐zonal and peripheral necrosis, have been observed in patients with sepsis14, 32. Liver function is depressed early after the onset of sepsis and inflammatory cytokines inhibit liver cell proliferation, promoting liver failure31, 33–36. In patients affected by acute liver failure, a clear correlation between sepsis, progression of encephalopathy and death has been described16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most cytokines, which rapidly disappear from the blood, IL‐18 persists in the blood for long periods. We reported the high involvement of IL‐18 in the development of acute hepatic failure and that IL‐18 is a good indicator of the severity of illness (4,5). NM is thought to inhibit IL‐18 production by inhibiting PAR‐2 activity.…”
Section: Discussionmentioning
confidence: 99%